Sintesis Bukti tentang Efikasi Diri dan Grit sebagai Prediktor Prestasi Akademik Mahasiswa: Tinjauan Sistematis - Yusdi Lastutiyanto; Fahri Ahmad Fauzi; Rilla Sovitriana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of educational psychology shows a shift from focusing on cognitive abilities to emphasizing non-cognitive factors such as self-efficacy and grit in explaining academic success. This study aims to analyze the relationship between self-efficacy and grit and their association with students’ academic achievement. The study employs a Systematic Literature Review (SLR) design with a qualitative-descriptive approach following the PRISMA framework. Data were obtained from the Scopus database using the keyword “self-efficacy AND grit”, resulting in 86 identified articles, of which 13 met the inclusion criteria. The findings indicate that self-efficacy has a consistent and more dominant relationship with various indicators of academic achievement, both directly and indirectly through variables such as engagement and learning strategies. Grit also contributes to academic success, but its influence tends to be indirect and mediated by self-efficacy. The discussion reveals that the relationship between self-efficacy and grit is reciprocal and forms a dynamic psychological system. This study concludes that self-efficacy plays a central role as a key mediator linking grit to academic achievement within an integrative conceptual framework.